2007
DOI: 10.1111/j.1360-0443.2007.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial to assess the efficacy and safety of a transdermal delivery system of nicotine/mecamylamine in cigarette smokers

Abstract: If adding mecamylamine to nicotine replacement therapy (NRT) improves the chances of success at stopping smoking, the results of this study suggest that the effect is very small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Although the short-term abstinence rates reported here are much lower than would be expected from NHS Stop Smoking Services , they are in line with other research in which similarly strict definitions of continuous abstinence (i.e., not even a puff) were used (e.g., Glover et al, 2007). Using this sample of smokers had benefits and drawbacks.…”
Section: Discussionsupporting
confidence: 81%
“…Although the short-term abstinence rates reported here are much lower than would be expected from NHS Stop Smoking Services , they are in line with other research in which similarly strict definitions of continuous abstinence (i.e., not even a puff) were used (e.g., Glover et al, 2007). Using this sample of smokers had benefits and drawbacks.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to a7-nAChR-specific antagonists, a9-nAChR-specific antagonists reduce ascending afferent excitatory pain pathway signaling and have been shown to have analgesic effects in in vivo studies (50,84). As shown in Table 1, several nicotinic antagonists have either launched or entered phase II clinical trials (85,86). Unfortunately, most of these antagonists can also cause a variety of side effects resulting from the lack of nAChR subtype specificity.…”
Section: Nachr Antagonists As Potential Agents For Molecular Cancer Tmentioning
confidence: 99%
“…Initial work on precessation treatment revealed that mecamylamine increased the efficacy of patch therapy toward 47.5% to 58% (from 27.5% to 29% when used without mecamylamine) [39]. However, a recent multisite controlled study showed that effect to be minimal at best [40]. Furthermore, the often intolerable side effects of mecamylamine, such as postganglionic effects (eg, orthostatic hypotension) and strong anticholinergic effects (eg, dry mouth and constipation) have limited its use to research settings.…”
Section: Nicotine Antagonistsmentioning
confidence: 98%